Cyber-Crime and its Effects on E-Commerce Technologies - Apau, Richard; Koranteng, Felix Nti; Gyamfi, Samuel Adu (Journal of Information, 2019)
Adoption and use of e-commerce technologies continue to rise because they provide access to global markets, offer a competitive advantage and increase the effectiveness of businesses. Safety and trust are important factors that affect users’ intentions and use of e-commerce technologies. Considering the upsurge of cyber-crime activities and the paucity of research in this domain particularly in developing countries, this paper investigated how cyber-crime perceptions affect users’ intention to conduct business via e-commerce technologies. Using a survey approach, an online questionnaire was distributed and data from 476 participants was rigorously analyzed using Partial Least Square Structural Equation Modelling. The paper extends the theory of reasoned action with relevant constructs; trust and cyber-crime perceptions. The relationships between the constructs were based on deductive reasoning from prior studies. The hypothesized model explained 33.1% of the variance in Attitude Towards Behavior and 41.5% of Consumers Intention to Purchase. The results indicate that trust in internet medium, attitude towards behavior, subjective norm and cyber-crime perceptions are significant predictors of intention to purchase using e-commerce. There was, however, no significant relationships between Trust of Ecommerce Sellers and Cyber Crime Perceptions as well as Trust of Ecommerce Sellers and Consumers Purchase Intention. The findings elucidate businesses and stakeholders on the impacts of trust and cyber-crime perceptions on users’ purchase intentions. It also inspires e-commerce technology developers to incorporate security features that reduce the vulnerability of these systems. Finally, the findings for this study are limited to respondents from Ghana hence future analysis could explore other countries.